2014
DOI: 10.2139/ssrn.2721753
|View full text |Cite
|
Sign up to set email alerts
|

Monetary and Fiscal Policy in Times of Crises: A New Keynesian Perspective in Continuous Time

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 86 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Supply-side shocks also caused total spending to respond adversely, and a contractionary budgetary policy was pursued. Therefore, It is believed that the outcome overlapped the conclusion that the nature of the interaction between both policies is substitute in nature this result can be seen in [18,19,67] which are thought to have shown that a shock that was experienced in the economy leads to a policy conflict.…”
Section: Impulses-response Analysis For Nigeriamentioning
confidence: 97%
See 1 more Smart Citation
“…Supply-side shocks also caused total spending to respond adversely, and a contractionary budgetary policy was pursued. Therefore, It is believed that the outcome overlapped the conclusion that the nature of the interaction between both policies is substitute in nature this result can be seen in [18,19,67] which are thought to have shown that a shock that was experienced in the economy leads to a policy conflict.…”
Section: Impulses-response Analysis For Nigeriamentioning
confidence: 97%
“…The coordination of fiscal and monetary strategies in Nigeria is by the government through the Federal Ministry of Finance and the Central Bank of Nigeria, respectively [11]. The relationship between monetary and fiscal policies remains a major point of contention in the literature as studies have revealed that fiscal and monetary policies can interact as substantial complement between both policies, that is expansionary measures in one policy are reinforced by those in the other [12,[13][14][15][16][17], other studies revealed that fiscal and monetary policies can also interact in a substitutive manner between both policies, that is expansionary measures in one policy are reinforced by contractionary measure in the other policy [18,19], although, the coordination between fiscal and monetary policies varies across countries and depends on their economic, political, and social situations [20]. However, the extent of their reliance, independence, and interdependencies determine whether the economy moves closer to or further away from predefined goals and targets [21,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Their empirical clarification reaffirms the role of policy timing in affecting inflation. Hayo and Niehof (2014) developed a DSGE model in an open economy with monetary and fiscal policy in a continuous time framework to analyze the interdependence between the two policies during financial crises. They analyzed the contagious effects on bond markets and real markets under different types of monetary and fiscal policies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study concludes that a tax reduction would be more potent during the liquidity trap than when there is no liquidity trap. Following the thoughts of Hayo and Niehof (2014) on the role of monetary and fiscal policy in fighting recessions or economic crises, Valdivia and Valdivia (2019) investigated the effectiveness of fiscal and monetary policy coordination during the 2007-2010 global crisis using a DSGE model. The results show that fiscal and monetary policies shocks have unfavourable impacts on price stability and economic growth during a crisis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Consequently, the fiscal authority is assumed to be good, and slashes in taxes funded by upsurges in debt level are recompensed by a surge in taxation at the latter date to ensure debt creditworthiness. Under this arrangement, the dispute on the coordination between the fiscal and monetary policies was said to be pointless (Hayo & Niehof, 2014). The customary duty of the central bank is to regulate price levels.…”
Section: Introductionmentioning
confidence: 99%